A generalized analytical model of gain bandwidth for design of optical parametric amplifiers - Qu, Shizhen (2021)
An analytical model is derived for calculating the maximum gain bandwidth of optical parametric amplifiers (OPA). The model relates in an explicit but simple way the gain bandwidth to the key design parameters of an optical parametric amplifier. It can be used as a tool to obtain the design parameters of an OPA capable of achieving the maximal gain bandwidth. The model is especially useful to design of long wavelength (>6μm)optical parametric amplifiers which have small difference between the center wavelengths of pump and signal.